Adaptive resilient observer-based control of leader-following smart vehicle platoons subject to compound cyber attacks - Chehardoli, Hossein; Shafie, Ehsan (International journal of dynamics and control, 2025)
In a smart vehicle platoon (SVP), by means of wireless technologies, each smart vehicle (SV) can exchange data and cooperate with other SVs to enhance safety, stability and efficiency of the traffic flow. Besides this, we know that steering and braking mechanisms are the last components of an SV control system, which have a significant role in guaranteeing the security of SVPs. However, these and other actuators of an SV cannot provide security guarantees versus hostile attacks. In an SVP, both actuators and communication links may be easily exposed to malicious attacks. In this work, we investigate the resilient consensus protocol of third-order SVPs subjected to both replay and actuator attacks. Replay attack will cause time delay in transferred data, and the actuator attack will inject faulty commands on control input. The replay attacks can be modeled as delayed data. Therefore, the closed-loop dynamics will be as a linear multiple-time delay system. The designed control law has two main parts: a nonlinear compensator which confronts the unknown bounded actuator attacks and a linear distributed observer which estimates the states of the leader. By presenting a Lyapunov–Krasovskii function and employing the Lyapunov theory, we will show that the estimation errors of leader states will vanish as well as the tracking error of each SV. Some simulation scenarios are given to depict the efficiency of that methodology.